PEMODELAN DIMENSI SAMPEL UNTUK MENENTUKAN PARAMETER DESAIN MENGGUNAKAN UJI TRIAKSIAL PADA TANAH LEMPUNG - Rabinah, Aiun Hayatu; Pamungkas, Nur Setiaji; Suparman, Suparman; Satriyadi, Lilik; Warsiti, Warsiti; Bulan, Yosua Daniel; Affani, Chelsea Dhiya (Politeknik Negeri Semarang, 2023)
Test selection is very influential in determining the design parameters. The aim of this research is to study the dimensions of the triaxial test soil sample on clay soils in the Semarang area to obtain soil shear parameters that can be used as design parameters. The tests include testing the physical and mechanical properties of the soil. Mechanical testing uses a triaxial test. The UU triaxial test sample is modeled with a diameter of 3.5 cm and 3.8 cm, while the CU sample is 3.5 cm. Based on the results of soil property index testing, sieve analysis, and consistency limits, it can be concluded that the soil samples are non-organic clay with high plasticity. Based on the triaxial test UU values of c and Ï… it can be seen that the largest shear parameter occurs in the specimen with a diameter of 3.8 cm. The largest UU triaxial test c value is 0.32 kg/cm2 , meanwhile, for Ï… it has a value of 11.65 º. The specimen with a larger diameter has a greater shear stress value. This can be influenced by larger c and Ï… values. The c and c' values of the triaxial CU test results were 0.32 kg/cm2 and 0.50 kg/cm2 respectively. While the values of Ï… and Ï…' are 9.89 º and 17.35 º respectively. The Ï„ and Ï„' values obtained were 1,394 kg/cm2 and 1,405 kg/cm2 , respectively. The modulus of elasticity of soil is 1500 kN/m2 and 3200 kN/m2 respectively which is included in the type of soft clay soil with a value range of 1800 ”“ 3500 kN/m2 and is included in the CH classification with a range of 0.35”“4 MPa. The value of the elastic modulus taking into account the value of cohesion, plasticity index, and OCR is closer to the prediction of soil elastic modulus values by Das